New challenges to health : (Cambridge University Press, 2001)
This book discusses the ecology of viruses with an emphasis on the emergence of devastating hemorrhagic diseases, and a review of the molecular and cellular basis of the pathogenesis of several viral diseases. The volume provides an introduction to the mathematical analysis of recurrent epidemic viral diseases and examines the neurological and psychological diseases in relation to the pathological mechanisms underlying prion disease. Chapters explore new viral threats including HIV, bunyaviruses, morbilliviruses and caliciviruses